Elevated CCL19/CCR7 Expression During the Disease Process of Primary Sjögren's Syndrome - Liu, Zhenwei; Li, Fengxia; Pan, Axiao; Xue, Huangqi; Jiang, Shan; Zhu, Chengwei; Jin, Mengmeng; Fang, Jinxia; Zhu, Xiaochun; Brown, Matthew A.; Wang, Xiaobing (Frontiers in Immunology, 2019)
Primary Sjögren's syndrome (pSS) is a common chronic autoimmune disease characterized by a high prevalence of autoantibodies and lymphocyte-mediated exocrine gland damage. To enhance our understanding of the mechanisms underlying the progression of the disease and to discover potential biomarkers for the early diagnosis of pSS, we applied RNA sequencing to compare the gene expression patterns in minor salivary glands between pSS patients and non-pSS. A total of 293 differentially expressed genes (DEGs) were detected in pSS vs. non-pSS (P < 0.05, fold changes > 2). Of these DEGs, 285 (97.26%) were up-regulated, with most being involved in immune system activation, especially in the formation of the immunological synapse. Significantly elevated CCL19/CCR7 expression in the salivary gland was found to be related to anti-Sjögren’s syndrome-related antigen A (SSA) antibody and IgG levels in pSS patients, which was further confirmed in a larger cohort. Up-regulated gene expression showed strong discriminatory accuracy in identifying pSS with area under the curve of 0.98 using receiver operating characteristic curve analysis. In conclusion, gene-expression changes in pSS include strong markers of immunological activation and have good discriminatory power in identifying patients with pSS.